Proyecto de inversión para el establecimiento de una productora de eventos musicales y de carácter social en la ciudad de Guayaquil - Merchán Pástor, Daniel Andrés (2009)
This project aims to investigate and justify the feasibility and establishment of a producer of musical events responsible for the organization, production and assembly of events and musical performances and a professional social service to be provided to event organizers, entrepreneurs, music promoters , the general public who wish to hire this service for implementation in the city of Guayaquil. The purpose will be to cover the requirements of the organization, production, logistics and assembly of launch marks, concerts, events, corporate parties, family celebrations, social gatherings, etc. Therefore an evaluation is carried out technical, financial and market for the constitution of the company and the equipment needed to start, development alternatives, and investment activities which generate an opportunity to comply effectively with an unmet need fully, an alternative to generate profits under a qualified staff. Also measure the level of profitability, pros and cons to operate.